Asian Organization for Crohn's and Colitis and Asia Pacific Association of Gastroenterology consensus on tuberculosis infection in patients with inflammatory bowel disease receiving anti‐tumor necrosis factor treatment. Part 2: Management. Issue 1 (28th December 2017) - Park, Dong Il; Hisamatsu, Tadakazu; Chen, Minhu; Ng, Siew Chien; Ooi, Choon Jin; Wei, Shu Chen; Banerjee, Rupa; Hilmi, Ida Normiha; Jeen, Yoon Tae; Han, Dong Soo; Kim, Hyo Jong; Ran, Zhihua; et al.
Abstract: Because anti‐tumor necrosis factor (anti‐TNF) therapy has become increasingly popular in many Asian countries, the risk of developing active tuberculosis (TB) among anti‐TNF users may raise serious health problems in this region. Thus, the Asian Organization for Crohn's and Colitis and the Asia Pacific Association of Gastroenterology have developed a set of consensus statements about risk assessment, detection and prevention of latent TB infection, and management of active TB infection in patients with inflammatory bowel disease (IBD) receiving anti‐TNF treatment. Twenty‐three consensus statements were initially drafted and then discussed by the committee members. The quality of evidence and the strength of recommendations were assessed by using the Grading of Recommendations Assessment, Development, and Evaluation methodology. Web‐based consensus voting was performed by 211 IBD specialists from nine Asian countries concerning each statement. A consensus statement was accepted if at least 75% of the participants agreed. Part 2 of the statements comprised three parts: (3) management of latent TB in preparation for anti‐TNF therapy, (4) monitoring during anti‐TNF therapy, and (5) management of an active TB infection after anti‐TNF therapy. These consensus statements will help clinicians optimize patient outcomes by reducing the morbidity and mortality related to TB infections in patients with IBD receiving anti‐TNF treatment.